Liq Fid “Dosificador Alimentario Para Pacientes Terminales” (2022)
This degree work focuses its research on the study of patients terminals related to cancer pathologies and the incidences that this disease has on the development of their quality of life. The characteristics that terminal patients possess are determined by the stages of functionality that measure independence in relation to a primary caregiver; the The causes that generate this problem are related to the treatment of the disease (chemotherapy), which has a high toxicity and damages the emotional state; and the another, to the degenerative factors of the same disease. On the other hand, there is the primary caregiver, who also sees the development of his daily life affected by the efforts and emotional exhaustion as a result of the "primary caregiver syndrome". The interest in the development of this degree project is related to the experience prior, as a motivating axis to relate Industrial Design with the areas of oncology and nutrition and dietetics. Professional interest in developing a strategy with relation of Food Design applied to the medical sector and the approach of a ramification methodology that allows linking health sectors with objective developments in the palliative care; the academic contribution will focus on breaking paradigms and skepticism about the acceptance of new methodological proposals in fields that require the input of Industrial design.